Organizational Change and Networked Learning: A structurational model - Marshall, Stewart; Gregor, Shirley (Proceedings of the International Conference on Networked Learning, 2000)
What structure and processes are needed to allow a university to exist and prosper in an age of globalization and rapid changes in the information technology underlying networked learning? This paper presents a model based on the structurational theory of information technology (Orlikowski and Robey, 1991). This model posits four relationships: (I) information technology is a product of human action; (2) information technology is an influence on human action; (3) organizational properties are an influence on human interactions with information technology; and, (4) information technology is an influence on the organization. The model is extended to include the market, technical and societal influences from the external environment that affect an organization. As an example of a university in Australia that is responding to the challenge of networked learning on a national and international basis, we examine Central Queensland University (CQU). It has been a distance education and on-campus education provider since 1974 and is now Australia's fastest growing university. Inherent in all CQU's operations is a model in which the organization, its members and its partners are all constituents of a network of learning facilitators.